Effect of video-based education on anxiety and satisfaction of patients undergoing spinal anesthesia - Meltem Cakmak; Isil Kose; Ciler Zinzircioglu; Yucel Karaman; Zeki Tuncel Tekgul; Sinan Pektas; Yelda Balik; Mustafa Gonullu; Pervin Sutas Bozkurt (Revista Brasileira de Anestesiologia)
Abstract Background: Providing sufficient information during a preanesthetic interview may help improve patient understanding and decrease anxiety related to spinal anesthesia. We investigated the effect of video-based education on anxiety and satisfaction in patients about to undergo spinal anesthesia. Methods: A total of 198 patients scheduled for minor elective surgery under spinal anesthesia were prospectively enrolled. The State-Trait Anxiety Inventory (State-Trait Anxiety Inventory/State and State-Trait Anxiety Inventory/Trait) questionnaires and visual analog scale were used to measure anxiety levels before the standard anesthesia evaluation was initiated. Then, 100 patients in Group 1 received written, verbal, and video-based education, whereas 98 patients in Group 2 received only written and verbal instructions regarding spinal anesthesia. Then all participants completed the State-Trait Anxiety Inventory/State and visual analog scale to evaluate anxiety. Finally, a 5-point Likert scale was used to measure satisfaction during postoperative period. Results: No differences were found in the State-Trait Anxiety Inventory/State, State-Trait Anxiety Inventory/Trait, or visual analog scale scores between the two groups before the information period. The State-Trait Anxiety Inventory/State scores evaluating anxiety during the post-information period were differed in both groups and they found as 36.5 ± 10.0 in Group 1 and 39.6 ± 8.6 in Group 2 (p = 0.033). The 5-point Likert scale scores to measure satisfaction were stated as 4.5 ± 0.6 in Group 1 and 3.5 ± 1.2 in Group 2 (p < 0.001). Conclusions: Providing video-based information during the preanesthetic interview alleviated anxiety and increased satisfaction in patients undergoing spinal anesthesia.